SPK PENGAMBILAN KREDIT RUMAH TANGGA DENGAN METODE BUDGETING BERBASIS ANDROID - Eka Nabela Putri, Desylia; SUKUR, MUJI (Information Technology and Telematics, 2018)
Abstract - A home for everyone is a major need to be met. However, not all families are able to fulfill them because their finances are not well managed. As a result, many families were heavily in debt.Therefore, the authors intend to develop a decision support system for making home loans with android based budgeting method. The budgeting method takes into account salary income and household expenditures.If a family wants a home purchase on credit,it is also necessary a decision support system in recommending a home in accordance with a family budget.DSS of household credit collection application can help the family in calculating the budget owned and get home recommendations in accordance with the financial owned